MODEL-MODEL POTENSIAL TANAM HUTAN RAKYAT DENGAN TANAMAN REMPAH DI KABUPATEN SUKABUMI, PROVINSI JAWA BARAT - Effendi, Dedi Soleh; Hoerudin, Hoerudin (Research Center for Biology-Indonesian Institute of Sciences, 2003)
Indonesia has great potentila in terms of community forest reaching more than 42 million ha. This potential, however, is still unwellmanaged so that is couldnt be a main source of farmersincome. In fact, according to argo ecology system; community forest can be cultivated by introducing promising intercrops in order to deliver more benefical effect. To overcome this problem, a reseach aiming to obtain potential models for community forest and spice crops intercropping pattern based on agro ecological zone was conducted from August to December 2000. The reseach was carried out on 1.000 ha of partnership-based community forest (Paraserianthes falcataria) in Lengkong and Tegalbuled Sub district,sukabumi Regency, West Java province. the objectives of the research were achieved through survey method in gathering primary and secondary data. The data were analyzed by using Expert system Program (version 3.2.2.) and Framework of Land Evaluation. the results showed that the community forest explored was devided into 6 agro ecological zones with 5 recommended-landuses. Those are forestry (Zone I), palntation (Zone IIlax and IIbx), agroforstry (zone IIIax and IIIbx), and upland cultivation (Zone IVax2). According to microlimate condition under P.Falacataria trees, bushy pepper (Piper nigrum) is the most promising intercorps. Meanwhile, framework of land evaluation revealed that Zingiber officinale, Amomum cardamomum, and other Zingiberaceae species were marginally suiltable accompanied by heavy texture as the main constraint. In short, the potential models were (1) P. falactaria + A. cardamomum; (2) P.falactaria + P.nigrum. (3) P.falactaria + Z.officianale and (4) P.falactaria + Zingiberaceae (Curcuma xanthorizza, C.domestica, and Kaemferia galanga). Model (1),(3) and (4) would be more suitable on zone IIIax,IIIbx, and IVax2, whereas model (2) should be on zone IIIax nad IVax2.